Pengaruh Integrasi Pembangkit Fotovoltaik (PV) terhadap Alokasi Kapasitor yang Optimal pada Jaringan Distribusi Energi Listrik - Astrid, Erita; Dani Solihin, Muhammad; Siregar, Rosma; Suryanto, Eka Dodi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Recent advances in renewable energy as well as changes in infrastructure and government regulations have driven the increasing use of distributed solar/photovoltaic power generation (PV) in the electricity distribution network. The integration of PV as one of the active power supply sources if not accompanied by reactive power compensation will cause increased power losses in the system and increase the risk of voltage instability. Therefore, along with the intensive use of PV, planning the allocation of capacitors as reactive power compensators is very necessary. This work examines the optimization of capacitor allocation and sizing by the Genetic Algorithm (GA) method, accounting for the uncertainties in photovoltaic output fluctuations. he emergence of uncertainty parameters in the problem formulation makes the analysis of power flow in the system must be carried out with a probabilistic technique. The outcomes of the power flow analysis, specifically the power losses within the system, will serve as the objective function for the optimization process where the purpose of this optimization is to minimize the resulting power losses. The proposed optimization is simulated on the IEEE 34 bus radial distribution system using Matlab. The results showed a reduction in losses of 53.18%, especially from 219.2 kW to 160 kW. In addition, this optimization scheme also identified suitable locations for installing capacitors, namely on buses 7, 8, 12, 21, 25, and 31.